"A Revolution Is a Force More Powerful Than Nature": Extreme Weather and the Cuban Revolution, 1959–64. Issue 3 (1st June 2020) - Wolfe, Mikael
Abstract: This article examines how the severe drought of 1961–62 and the fury of Hurricane Flora in October 1963 influenced the Cuban Revolution socioeconomically and geopolitically in the crucial first five years of Fidel Castro's consolidation of power. Based on extensive research in US and Cuban newspapers and journals, declassified US government documents, the speeches, interviews, and writings of Cuban revolutionaries and foreign advisers, oral histories of hurricane survivors, and secondary literature, this article employs an environmental history approach to show that the governments and media of both Cuba and the United States perceived environmental and geopolitical factors as being intertwined when explaining Cuba's socioeconomic travails. Although weather events alone did not determine the progression of the Cuban Revolution, their varied effects nevertheless shaped the formative years of the revolution by influencing Cold War-era national development in ways that scholars of early revolutionary Cuba have largely overlooked.